Investigation of multilayer tribological coatings on CuSn10Pb10 bronze produced by electrospark alloying - Haponova, Oksana; Tarelnyk, Viacheslav; Tarelnyk, Nataliia; Laponog, Gennadii; Smolenko, Stanislav; Mościcki, Tomasz (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
Bronzes are widely used as anti-friction materials in sliding units. However, their performance depends heavily on the condition and structure of the surface layer. This study investigates the formation of multilayer antifriction coatings on CuSn10Pb10 bronze by electrospark alloying (ESA) using silver, lead, and tin electrodes. ESA was conducted in a sulphur-containing technological medium. Two technological schemes were implemented: conventional multilayer alloying (Ag → Pb → Ag and Ag → Sn → Ag) and alloying using a sulphur-containing medium ((S + Ag) → Pb → (S + Ag) and (S + Ag) → Sn → (S + Ag)). The microstructure, microhardness, surface roughness, and elemental distribution in the formed layers were investigated using optical microscopy, scanning electron microscopy with energy-dispersive analysis, and microhardness measurements. The tribological properties of the coatings were evaluated using a ball-on-disk configuration. It was determined that ESA produces a multilayer structure consisting of an outer layer, a bright sublayer, a heat-affected zone, and the substrate. The bright sublayer exhibited the highest microhardness values due to intensive material mixing and rapid melt solidification. The lowest friction coefficients (µ = 0.095−0.148) were obtained for sulphur-containing coatings. Introducing sulphur reduces the friction force by an average of 19%, due to a decrease in the adhesive component of friction and suppression of contact seizure.